HUBUNGAN KEPRIBADIAN TIPE-D DENGAN KOPING KLIEN AKNE VULGARIS DI JURUSAN KEPERAWATAN POLITEKNIK KESEHATAN KEMENKES MANADO - Jon W. Tangka; Femmy Lumi; Selny Ponge (POLTEKKES KEMENKES MANADO, 2014)
This study aims to identify the relationship of type-D personality with clients coping acne vulgaris. The research method using descriptive analytic cross sectional design, the 120 respondents polytechnic nursing students of Department of Health MoH Manado, period study from April to July 2014. The instrument used was a questionnaire-type-D personality and coping questionnaire. Univariad analysis using frequency distributions are presented in tables and bivariate analysis using Chi-Square. The results of Chi-square analysis with significance level of 95% at α 5% (α = 0.05), obtained by X ² = 13.308 with p (asypm.sig) = 0.000, <0.005, means that there is a significant association between type-D personality in coping clients of acne vulgaris. Conclusion: Type-D personality proved significantly associated with clients coping acne vulgaris, and individuals with a type-D personality tend to have maladaptive coping. Suggestion: the need for student research development of type-D personality and motivation in facing the problem of acne vulgaris